Regeneration of alveolar ridge defects. Consensus report of group 4 of the 15th European Workshop on Periodontology on Bone Regeneration. (18th June 2019) - Jepsen, Søren; Schwarz, Frank; Cordaro, Luca; Derks, Jan; Hämmerle, Christoph H. F.; Heitz‐Mayfield, Lisa J.; Hernández‐Alfaro, Federico; Meijer, Henny J. A.; Naenni, Nadja; Ortiz‐Vigón, Alberto; Pjetursson, Bjarni; Raghoebar, Gerry M.; et al.
Abstract: Background and Aims: Bone augmentation procedures to enable dental implant placement are frequently performed. The remit of this working group was to evaluate the current evidence on the efficacy of regenerative measures for the reconstruction of alveolar ridge defects. Material and Methods: The discussions were based on four systematic reviews focusing on lateral bone augmentation with implant placement at a later stage, vertical bone augmentation, reconstructive treatment of peri‐implantitis associated defects, and long‐term results of lateral window sinus augmentation procedures. Results: A substantial body of evidence supports lateral bone augmentation prior to implant placement as a predictable procedure in order to gain sufficient ridge width for implant placement. Also, vertical ridge augmentation procedures were in many studies shown to be effective in treating deficient alveolar ridges to allow for dental implant placement. However, for both procedures the rate of associated complications was high. The adjunctive benefit of reconstructive measures for the treatment of peri‐implantitis‐related bone defects has only been assessed in a few RCTs. Meta‐analyses demonstrated a benefit with regard to radiographic bone gain but not for clinical outcomes. Lateral window sinus floor augmentation was shown to be a reliable procedure in the long term for the partially and fully edentulous maxilla. Conclusions: The evaluated bone augmentation procedures were proven to be effective for the reconstruction of alveolar ridge defects. However, some procedures are demanding and bear a higher risk for post‐operative complications.